Hubungan Antara Keragaman Gulma dengan Penyakit Bulai pada Jagung (Zea mays L.) Stadium Pertumbuhan Vegetatif - SUDARMA, I MADE; SUADA, I KETUT; AYU YULIADHI, KETUT (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012))
Weeds play an important role in the spread of downy mildew disease, competition, and lower crop yields of corn. Research using the survey method in 3 locations of Sanur village, Denpasar City. Each location is taken 5 samples, and each sample area was 1m2, which was arranged diagonally. For weeds identification was using reference i.e. Weeds of rice in Indonesia, and identification of downy mildew disease using reference i.e. Maize Disease: A Guide for Field Indentification and microscopically, while the weeds diversity was determined based on Diversity Index of Shannon-Wiener. Relationship between number of weed species and weed populations, and disease incidence were determined by regression and correlation analysis. Weed diversity on ecosystem of maize in vegetative stage is very low with the diversity index of 0.779, this means weed ecosystem unstable, and dominated by a particular weed species was Paspalum commersonii Lamk. (Fam. Poaceae/Graminaceae) of 23.3%, with the dominance index of 0.709. Relationship between the number of weed species and disease incidence of the downy mildew disease was highly significant (P<0,01), while the relationship between weed population and disease incidence of the downy mildew disease is not significant. Plant height and leaf number of maize was influenced by the type of weed, but weed populations only affect plant height of maize in vegetative stage (V3-V11).
Keywords: weeds diversity, disease incidence, vegetative stage